Activity budgets of Common Eiders in different housing environments - Prescott, Jacques (Wildfowl, 1981)
When kept in two different captive environments, 19 Common Eiders Somateria m. mollissima showed striking differences in their activity budgets. In a large outdoor enclosure, locomotion and feeding were significantly more frequent than in a smaller indoor pen, and the birds spent more time in the water. Time spent preening did not differ.